Ação do extrato de chá verde no estado oxidativo de ratos com artrite induzida por adjuvante - Gonçalves, Geferson de Almeida (2015)
The purpose of the study was to evaluate the possible effects of the administration of a green tea extract on the oxidative state of adjuvant-induced arthritic rats. Daily doses of 250 mg/Kg (59.8 mg catechins per Kg) during 23 days were administered by gavage. This treatment produced significant diminutions in protein and lipid damage in liver, brain and plasma. It also diminished the tissue ROS contents and increased the antioxidant capacity of the plasma. The antioxidant defenses, which are diminished by arthritis, were improved by the green tea treatment, as revealed by the restoration of the GSH and protein thiol levels and by the strong tendency of normalizing the activities of the antioxidant enzymes. The green tea treatment also tended to normalize the plasma albumin levels. It was concluded that green tea consumption is possibly beneficial for patients suffering from rheumatoid arthritis because it attenuates injury to lipids and proteins.